Studies on French Bean (Phaseolus vulgaris L.) Varieties under Different N, P, K and S Levels for Growth, Yield and Economics - Sharma, B K; Kushwah, S S; Verma, K S; Singh, O P (Journal of Horticultural Sciences, 2013)
Fifteen combinations of three French bean varieties viz., Arka Komal (V1), Swaran Priya (V2) and Contender (V3) and five fertilizer levels (F1- 20:40:40:20kg/ha NPKS; F2- 40:40:40:20kg/ha NPKS; F3 - 60:60:60:40kg/ha NPKS; F4 - 80:60:60:40kg/ha NPKS, and F5 -100:80:80:50kg/ha NPKS) were tested in factorial Randomized Block Design, with three replications. Among the varieties, Swaran Priya was superior for growth attributes, yield attributes and yield. Among fertilizer levels, F5 (100:80:80:50kg/ha NPKS) resulted in highest growth parameters, yield parameters and yield of pods. Economic evaluation showed that variety Swaran Priya under F5 (100:80:80:50kg/ha NPKS) resulted in maximum gross returns, net returns and cost:benefit ratio for green pod production.